2023
DOI: 10.1002/smi.3240
|View full text |Cite
|
Sign up to set email alerts
|

Families under pressure: A qualitative study of stressors in families of children with congenital heart disease

Abstract: The objective of this study was to better understand the stressors in families of children with congenital heart disease (CHD) to assist with formulating targeted stress management plans for such families. A descriptive qualitative study was undertaken at a tertiary referral hospital in China. Following purposeful sampling, interviews were conducted with 21 parents of children with CHD regarding the stressors in their families. Following content analysis, 11 themes were generated from the data and categorised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…However, many studies highlight the importance of early psychological support for parents, and in particular for mothers, to reduce maternal prenatal stress and optimize disease management [14]. Zhang et al [31] suggested that confusion and lack of understanding about the diagnosis of CHD can bring stress to the family, and for this reason early psychological support combined with education about the disease is fundamental to help families. Although there is no evidence on this subject, one possibility would be to promote Behavioral Cardiology for patients' disease management [32].…”
Section: Psychological Support For Parents During Pregnancy and After...mentioning
confidence: 99%
“…However, many studies highlight the importance of early psychological support for parents, and in particular for mothers, to reduce maternal prenatal stress and optimize disease management [14]. Zhang et al [31] suggested that confusion and lack of understanding about the diagnosis of CHD can bring stress to the family, and for this reason early psychological support combined with education about the disease is fundamental to help families. Although there is no evidence on this subject, one possibility would be to promote Behavioral Cardiology for patients' disease management [32].…”
Section: Psychological Support For Parents During Pregnancy and After...mentioning
confidence: 99%